2007
DOI: 10.1007/s11664-007-0335-x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Lanthanum Doping on the Microstructure of Tin-Silver Solder Alloys

Abstract: In this study, quantitative microstructure studies were performed on multiple length scales to investigate the effect of lanthanum (La) doping on Sn-Ag leadfree solder materials. Factors considered in this paper include doping amount, aging temperature, and aging time. It was found that La doping reduces the grain size significantly, and the reduced grain size remains stable during thermal aging. The size of the Ag 3 Sn particles is also greatly reduced by La doping, and the particles coarsen during thermal ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
4
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 15 publications
4
4
1
Order By: Relevance
“…Moreover It was also observed that quantity La5Sn3 IMC depend upon the concentration La doping i.e. with high 0.5wt% of lanthanum bigger snowflakes has be observed as shown in Figure 8 while small isolated snow can be seen with less La doping which is consistent with the results of Min et al [25].…”
Section: Sac305supporting
confidence: 88%
See 4 more Smart Citations
“…Moreover It was also observed that quantity La5Sn3 IMC depend upon the concentration La doping i.e. with high 0.5wt% of lanthanum bigger snowflakes has be observed as shown in Figure 8 while small isolated snow can be seen with less La doping which is consistent with the results of Min et al [25].…”
Section: Sac305supporting
confidence: 88%
“…Moreover It was also observed that quantity La5Sn3 IMC depend upon the concentration La doping i.e. with high 0.5wt% of lanthanum bigger snowflakes has be observed as shown in Figure 8 while small isolated snow can be seen with less La doping which is consistent with the results of Min et al [25].La doping greatly reduces the Ag 3 Sn and Cu 6 Sn 5 particle size particle during thermal aging. Surface area averaged particle size of Cu 6 Sn 5 particles was obtained as per ASM handbook [95].…”
supporting
confidence: 87%
See 3 more Smart Citations